First Report of Kosakonia cowanii Causing Bacterial Blight on Amorphophallus konjac in China - Chu, Honglong; Dong, Kun; Chen, Chen; Su, Xuelian; Zhao, Qin; Gao, Yong; Zhang, Yanan (Plant disease, 2025)
Amorphophallus konjac, commonly known as konjac, has significant economic and medicinal value, particularly in Asian countries (Gao et al. 2022). In July 2024, an outbreak of leaf blight was observed in a one-hectare field in Fuyuan (25.67°N; 104.25°E), Yunnan, China. The disease manifested as brown lesions starting at the leaf tips or edges, which rapidly darkened and expanded, leading to leaf necrosis. In severe cases, the disease affected the overall plant health, reducing corm yield and quality significantly. To isolate the causal agent, six diseased leaves from six plants were surface disinfected, and the junction region of healthy and diseased tissues was excised and homogenized in a 15-ml sterile centrifuge tube with 2 ml of sterile distilled water. The resulting bacterial suspension was serially diluted to 10-5 and 200 μl of the diluted sample was spread on LB agar plates. Three pure cultures (designated MY1, MY2, and MY3) were obtained through successive streaking. The isolated colonies were light yellow, convex, and nearly round in shape. Genomic DNA from the three pure isolates was extracted and used to amplify partial sequences of 16S ribosomal RNA (16S rRNA) with primers 27F/1492R (Brady et al. 2008), the beta-subunit of RNA polymerase (rpoB) using primers CM81-F/CM32b-R (Polz and Cavanaugh 1998), and the DNA gyrase subunit B (gyrB) with primers UP-1/UP-2r (Yamamoto and Harayama 1995). The sequences for 16S rRNA (accession nos. PQ288765-PQ288767), rpoB (PQ304887-PQ304889), and gyrB (PQ304884-PQ304886) were deposited in GenBank. Nucleotide BLAST analysis showed that the rpoB, gyrB and 16S rRNA sequences of isolate MY1 shared 99.36, 98.89 and 99.86% identity with those of K. cowanii strains (EU629168, CP107077 and OR121838), respectively. Furthermore, a multigene phylogenetic analysis revealed a strongly supported clade including strain MY1, MY2, MY3 and other K. cowanii isolates. To test pathogenicity, a greenhouse experiment was conducted using five four-month-old healthy A. konjac plants grown in pots. For each plant, three leaves were inoculated with a bacterial suspension of strain MY1 (108 CFU/ml) via leaf infiltration. Another set of three leaves were infiltrated with sterile water as controls. These plants were enclosed in plastic bags for 24 hours post-inoculation. Inoculated plants initially exhibited brown lesions with a yellow halo, which subsequently developed into dark symptoms within seven days. Control plants remained symptom-free. This experiment was repeated three times with consistent results. K. cowanii was reisolated from infected leaves and identified based on Sanger sequencing of 16S rRNA, thus fulfilling Koch's postulates. In recent years, K. cowanii has been confirmed to cause fruit blotch on Trichosanthis fructus (Chen et al. 2024), stalk rot in foxtail millet (Han et al. 2023), bacterial wilt on patchouli (Zhang et al. 2022), and bacterial blight on soybean (Krawczyk and Borodynko-Filas 2020). To our knowledge, this is the first report of K. cowanii causing leaf blight on A. konjac worldwide. This study identifies a previously unrecognized disease affecting konjac production. The identification of the causal agent provides essential information for the diagnosis and management of this disease.